EKSISTENSI HUKUM PERAWAT SEBAGAI TENAGA KESEHATAN SELAIN TENAGA KEFARMASIAN TERHADAP HAK ATAS PELAYANAN KESEHATAN - Winda Wijayanti (Faculty of Law, Universitas Jenderal Soedirman, 2013)
Health is one of the human rights guaranteed in Article 28H paragraph (1) of The 1945 Constitution of The Republic of Indonesia that state is responsible to respect, protect, and fulfill its implementation. Health Act is a manifestation of the right to health services to improve public health based on the principles of non-discriminatory, participatory, and sustainable. One of the nurses as health professionals working in remote and difficult to reach in a dilemma in the form of a very limited authority to health personnel, in addition to pharmacy personnel, associated with pharmacy practice set out in Article 108 paragraph (1) of the Health Act and Explanation, while in others there is the threat of the sanction of imprisonment or fines provided for in Article 190 paragraph (1) if the Health Act deliberately did not provide help to patients in emergencies. Constitutional Court has decision that in the Health Act.Keywords: health, health workers, nursing, constitutional court